Observation of a Neutral Structure near the D(D)over-bar* Mass Threshold in e(+)e(-) -> (D(D)over-bar*)(0)pi(0) at root s=4.226 and 4.257 GeV - Çetin, Serkant Ali (Amer. Physical Soc., 2015)
A neutral structure in the D (D) over bar* system around the D (D) over bar* mass threshold is observed with a statistical significance greater than 10 sigma in the processes e(+)e(-) -> D+D*(-)pi(0) + c.c. and e(+)e(-) -> D-0(D) over bar*(0)pi(0) + c.c. at root s = 4.226 and 4.257 GeV in the BESIII experiment. The structure is denoted as Z(c)(3885)(0). Assuming the presence of a resonance, its pole mass and width are determined to be [3885.7(-5.7)(+4.3) (stat) +/- 8.4(syst)] MeV/c(2) and [35(-12)(+11) (stat) +/- 15(syst)] MeV, respectively. The Born cross sections are measured to be sigma[e(+)e(-) -> Z(c)(3885)(0)pi(0); Z(c)(3885)(0) -> D (D) over bar*] = [77 +/- 13(stat) +/- 17(syst)] pb at 4.226 GeV and [47 +/- 9(stat) +/- 10(syst)] pb at 4.257 GeV. The ratio of decay rates B[Z(c)(3885)(0) -> D+D*(-) + c.c.]/B[Z(c)(3885)(0) -> D-0(D) over bar*(0) + c.c.] is determined to be 0.96 +/- 0.18(stat) +/- 0.12(syst), consistent with no isospin violation in the process, Z(c)(3885)(0) -> D (D) over bar*.
Keywords: DECAY